2015
DOI: 10.2319/051015-318.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontics is temporomandibular disorder–neutral

Abstract: Objectives: To assess if subjects with a clinical diagnosis of temporomandibular disorders (TMDs) have a similar prevalence of orthodontic history as a population of TMD-free individuals and to assess if those subjects who have a history of ideal orthodontics have fewer symptoms than those with a history of nonideal orthodontics. Materials and Methods: Two groups of age-and sex-matched individuals belonging to either a study ("TMD") or a control group were recruited. Subjects who underwent orthodontic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 22 publications
3
40
0
7
Order By: Relevance
“…A similar conclusion can be reached in the case of sagittal skeletal profiles that are associated with an increased risk for disc displacement . Such suggestion is in line with recent observations that orthodontics is neutral as far as the temporomandibular disorders are concerned . Similar suggestions have been proposed also for the purported relationship between anterior open bite and TMJ osteoarthrosis, with the former being the consequence, rather than the cause, of the latter .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A similar conclusion can be reached in the case of sagittal skeletal profiles that are associated with an increased risk for disc displacement . Such suggestion is in line with recent observations that orthodontics is neutral as far as the temporomandibular disorders are concerned . Similar suggestions have been proposed also for the purported relationship between anterior open bite and TMJ osteoarthrosis, with the former being the consequence, rather than the cause, of the latter .…”
Section: Discussionsupporting
confidence: 86%
“…A purported causal relationship between ‘malocclusion’ and TMDs has been advocated for years by the precepts of gnathology , but the occlusal paradigm for TMD has never been convincingly validated . Observations that conservative management of TMD symptoms is almost always enough to achieve positive outcomes , and that chronic pain subjects are individuals with specific personality, and not occlusal, profiles , support the concept of neutrality as far as the effects of occlusal therapies on TMDs are concerned .…”
Section: Introductionmentioning
confidence: 99%
“…This study confirmed the substantial absence of clinically significant effects of orthodontics regarding the cause of TMD 20 .…”
Section: Discussionsupporting
confidence: 74%
“…Longitudinal, retrospective and cross sectional studies comparing the incidence of TMD in patients with and without a history of orthodontic treatment cannot demonstrate causality, but may highlight possible associations. Where such studies have taken place, they have failed to show an association between orthodontic therapy and TMD . However, evidence is emerging that there could be a subset of patients who have a genetic predisposition to TMD from orthodontics .…”
Section: Temporomandibular Disordermentioning
confidence: 99%